Keanekaragaman Serangga Pada Tanaman Sorgum Genotip Watar Hammu Witing Walla dan Wattar Hammu ManipaTadda - Glorius Paskan Danu; Ruth Meike Jayanti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study was conducted to evaluate the diversity of insect communities associated with sorghum plants of the genotypes Watar Hammu Witting Walla and Watar Hammu Manippa Tadda. Sampling was carried out using a Z-shaped transect method on both genotypes. Each genotype was represented by five replications, with every replication consisting of five plots, resulting in a total of 25 plots per genotype or 50 plots in total. Within each plot, six Yellow Sticky Traps were placed at representative points following the Z transect pattern to ensure systematic and comprehensive sampling. The traps were installed in the morning at approximately 07:00 a.m. and left in the field until 05:00 p.m. on the same day. After collection, insects adhered to the traps were gathered and stored in clear plastic bags for subsequent identification in the laboratory. The results of the analysis showed that the diversity index of the WH Witting Walla genotype was 1.54, while that of the WH Manippa Tadda genotype was slightly higher at 1.62. The dominance index values were 0.29 and 0.28, respectively, both of which are categorized as moderate. Across both genotypes, 13 insect genera were identified, including Musca, Bactrocera, Phaenicia sericata, Condylostylus longicornis, Bemisia, Bathrogia, Nezara, Camponotus, Abispa, Coleomegilla, Coccinella, Pieris rapae, Spodoptera, and Oxya. Among these, Musca sp. (housefly) and Bemisia sp. (whitefly) were the most dominant species, followed by Spodoptera sp. and Oxya sp. These findings suggest that insect communities on both sorghum genotypes exhibit moderate diversity and balanced dominance, indicating a relatively stable ecosystem.